Writing an Effective Medical Manuscript and Avoiding Errors for Smooth Publication - Bukhari, Mulazim Hussain (Annals of King Edward Medical University, 2023)
Writing for a biomedical journal is an important part of completing a research project. It is vital to publish original articles or other types of articles in various medical journals. This can be a challenging process, and it requires a sense of responsibility. The process starts with conceiving an idea, forming and conducting the research, and writing about the results, before finally getting it published. Before beginning to write a paper, the language must be properly structured and technical details must be included. Additionally, a cover letter must is sent to the journal's chief editor, mentioning any ethical considerations.